Optimizing ground control points for UAV photogrammetry: A case study in slope stability mapping - Ridha, Muhammad Hafizhir; Arifin, Yulian Firmana; Abdi, Ari Surya (Communications in Science and Technology, 2025)
This study investigated the effect of Ground Control Point (GCP) distribution on the accuracy of UAV-based slope mapping and stability analysis. Three GCP configurations—top-only, vertical, and diagonal—were tested. Accuracy was evaluated using UAV photogrammetry and compared to GPS geodetic data. The vertical GCP setup produced the highest accuracy, reducing total RMSE by 89.6% (from 52.93 mm to 5.50 mm). The diagonal configuration, while being slightly less accurate (61.26 mm RMSE), improved spatial coverage. Slope stability analysis using the finite element method (FEM) confirmed the reliability of the vertical setup for slope assessment. These results demonstrated that optimizing GCP layout could significantly improve model precision while reducing fieldwork. This work contributes to efficient and accurate slope monitoring with fewer GCPs, making it suitable for large-scale geotechnical applications. Future research will focus on applying these configurations to vegetated and more complex terrains and integrating automation for broader and scalable implementation.